Couple Resilience dan Well Being pada Dual Earner Family - Nadhifa, Pocut; Mawarpury, Marty; Afriani, Afriani; Sari, Novita (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2024)
Various problems that occur in dual earner families can affect the wellbeing of family members, therefore this study aims to determine the relationship between couple resilience and wellbeing in dual earner families. This study used a quantitative approach with a correlation method involving 50 couples as research samples.Data collection employed simple one-stage cluster sampling, and the data were gathered using two scales: the Couple Resilience Inventory (CRI) and the Centeredness Theory Scale (CT Scale). Data analysis was conducted using the Spearman correlation technique. The research findings indicate that several dimensions of couple resilience have a positive correlation with wellbeing. Specifically as follows: the correlation between couple resilience and husbands and wives wellbeing is (r= 0.292), the correlation between couple resilience and husbands wellbeing is (r = 0.464), and the correlation between couple resilience and wives wellbeing is (r = 0.377). Conversely, negative correlations were found between wive,s positive couple resilience and husbands wellbeing (r = -0.464), husbands positive couple resilience and husbands wellbeing (r = -0.514), and wives negative couple resilience and wives wellbeing (r = -0.427). No significant relationships were found between wives negative couple resilience and husbands wellbeing, as well as between husbands positive couple resilience and wives wellbeing.Berbagai permasalahan yang terjadi pada dual earner family dapat mempengaruhi wellbeing anggota keluarga oleh karena itu penelitian ini bertujuan untuk mengetahui hubungan couple resilience dan wellbeing pada dual earner family. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasi yang melibatkan 50 pasangan sebagai sampel penelitian. Teknik pengumpulan data menggunakan simple one-stage cluster sampling, data penelitian dikumpulkan menggunakan dua skala yaitu Couple Resilience Inventory (CRI) untuk mengukur Couple Resilience sedangkan untuk mengukur wellbeing menggunakan Centeredness Theory Scale (CT Scale). Analisis data menggunakan teknik korelasi Spearman. Hasil penelitian menemukan bahwa beberapa dimensi couple resilience berkorelasi secara positif dengan wellbeing yaitu couple resilience negative suami dan wellbeing istri menunjukkan nilai koefisien korelasi sebesar (r=0.292), couple resiliene negative suami dan wellbeing suami (r=0.464), couple resilience negative istri dan wellbeing istri (r=0.377). Sedangkan yang berkorelasi negatif pada couple resilience positive istri dan wellbeing suami dengan korelasi sebesar (r=-0.464), couple resilience positive suami dan wellbeing suami (r=-0.514), couple resilience negative istri dan wellbeing istri (r=-0.427). Sementara couple resilience negative istri dan wellbeing suami serta couple resilience positive suami dan wellbeing istri tidak memiliki hubungan.